Representativeness of EXPLORER-HCM trial and prevalence of eligibility criteria for Mavacamten in a nationwide cohort. (3rd October 2022) - Brandao, M; Goncalves Almeida, J; Fonseca, P; Faria, R; Sousa, O; Fonseca, C; Fontes-Carvalho, R
Abstract: Introduction: The EXPLORER-HCM trial evaluated the safety and efficacy of Mavacamten, a cardiac myosin inhibitor, in symptomatic obstructive hypertrophic cardiomyopathy (HCM). Mavacamten improved symptoms, exercise capacity and left ventricular outflow tract (LVOT) obstruction. However, the proportion of patients eligible for this therapy in real practice remains unclear. Purpose: To determine the prevalence of eligibility criteria for Mavacamten and to describe the profile of patients complying with EXPLORER-HCM criteria in a nationwide cohort. Methods: Cross-sectional study including all HCM patients enrolled in a European country-based nationwide registry. Presence of EXPLORER-HCM inclusion [≥18 years, obstructive HCM (LVOT gradient ≥50 mmHg), left ventricular ejection fraction (LVEF) ≥55%, New York Heart Association (NYHA) class II–III] and exclusion criteria [syncope or sustained ventricular tachycardia with exercise] were analyzed. Results: Of 1042 patients included in this analysis (57.8% male, mean age at diagnosis 52 years, 39.6% obstructive HCM), 45 met the EXPLORER-HCM inclusion criteria and, after applying exclusion criteria, 30 patients were eligible for therapy with Mavacamten. Eligible patients were all Caucasian, mostly female (63.3%), with a mean age at diagnosis of 58±14 years. All patients presented with heart failure symptoms, and were mostly in NYHA class II (83.3%); 4 patients (13.3%) presented with atrial fibrillation. In the baseline echocardiogram, mean LVEF was 68±9%; mean interventricular septum thickness was 20±4 mm; most patients presented with systolic anterior motion of the mitral valve (96.7%) and mitral regurgitation (96.7%). In cardiac magnetic resonance imaging evaluation, maximal wall thickness was 22±4 mm and 76.9% had late gadolinium enhancement. A pathogenic or likely pathogenic HCM gene variant was identified in 5 patients (MYH7 and MYBPC3 gene mutations). In this group, 86.2% of patients were treated with beta-blockers and 34.5% with calcium channel antagonists. Only 1 patient was on Disopyramide. Septal reduction techniques were used in 43.3% of patients: alcohol septal ablation and septal myectomy were performed in 7 (23.3%) and 6 (20.0%) patients, respectively. Cardioverter-defibrillators were implanted in 2 patients for primary prevention of sudden cardiac death, and 6 patients received a pacemaker for bradycardia indications. Conclusion: Specific therapies remain an unmet need in HCM. In this large nationwide cohort, only 2.9% of patients were eligible for therapy with Mavacamten according to EXPLORER-HCM criteria. Among patients complying with the study criteria, invasive septal reduction therapies were offered to a high proportion of patients. Further real-world data are warranted to estimate the proportion of HCM patients that will benefit from Mavacamten. Funding Acknowledgement: Type of funding sources: None.